Integration and Power-Sharing: What are the Future Options for Armed Non-State Actors in the Myanmar Peace Process?. Issue 1 (4th December 2015) - Kyed, Helene Maria; Gravers, Mikael
Myanmar is confronted with a contested peace process after over six decades of armed conflict between the national army and around 20 ethnic Armed Non-State Actors (ANSAs) in the country's resource rich borderlands. Although a Nationwide Ceasefire Agreement (NCA) was signed by eight ANSAs in October 2015, other groups have not, and fighting continues in some areas. A key controversy is insecurity about the future political and economic positions of the ANSAs, along with mistrust in the army's commitment to peace. In this article we discuss five re-integration options for ANSA members, including not only economic integration, but also integration into political parties, local government, civil society organisations and the security sector. We argue that conventional DDR programming is unrealistic in Myanmar, because the ANSAs are strongly opposed to any disarmament and demobilization before a far reaching political settlement towards federalism is reached. This calls for a more flexible sequencing of DDR that begins with reintegration options or what has been called RDD. In addition, reintegration efforts should not only be technical exercises, but be firmly embedded in disaggregated power-sharing guarantees, including for lower- and middle-ranking ANSA members at the local level. This will not only support more sustainable peace, but also help build more trust in the peace process. We conclude the article by considering the role of the international community.